Cahaya Chris Woodford ; alih bahasa, Andri Setyawan ; penyunting, Aburiyati, Rudiyanto, B. Waluyo - WOODFORD, Chris; Setyawan, Andri; Aburiyati; Rudiyanto; Waluyo, B (Pakar Raya, 2006)
40 hlm ilus 25 cm